(untitled) (American Journal of Language, Literacy and Learning in STEM Education (2993-2769), 2024)
Individualization in teaching English for Specific Purposes (ESP) involves tailoring instruction to meet the unique needs and goals of each student. This approach enhances student motivation, improves learning outcomes, and fosters greater autonomy. Strategies for individualization include needs assessments, personalized learning plans, differentiated instruction, choice boards, real-world materials, project-based learning, and technology-enhanced learning. Overcoming challenges such as time constraints, teacher workload, and student resistance is essential for successful implementation of individualized ESP instruction.